PENINGKATAN PRESTASI HASIL BELAJAR MATA PELAJARAN PEMBIAKAN TANAMAN SECARA VEGETATIF DENGAN MENGGUNAKAN METODE BERPIKIR, BERKELOMPOK, DAN BERBAGI (THINK PAIR AND SHARE) PADA SISWA KELAS X ATP SMK NEGERI 6 TAKALAR - Arifin, Tuti Handayani; Rera, Fiskia; Yanto, Subari (Universitas Negeri Makassar, 2016)
The objectives of classroom action research is to find out how far the achievement results of student of class X ATP SMK Negeri 6 Takalar after Think, Pair, and Share methods are applied. This research is a classroom action research conducted in two cycles. The first cycle conducted four times and the second cycle conducted two times. The research subjects were all students of class X ATP consists of 24 students. Data were analyzed using quantitative and qualitative data. The results concluded that the used of Think, Pair, and Share methods can improve the performance results of class X ATP SMK Negeri 6 Takalar. Student achievement increased measured by evaluation test of the first and second cycle